The Effect of Work Discipline and Financial Motivation on Employee Performance with Organizational Commitment as a Mediating Variable at Putra Celagi Rolling Pork in Bali - I Wayan PARIASA (PT Keberlanjutan Strategis Indonesia, 2025)
The culinary industry in Bali is growing rapidly along with the increasing tourism and lifestyle trends of the community. In the tight business competition, employee performance is an important factor in maintaining service quality. Babi Guling Putra Celagi business faces challenges in the form of high absenteeism, indiscipline, and problems in financial motivation and organizational commitment. This study aims to analyze the effect of work discipline and financial motivation on employee performance with organizational commitment as a mediating variable. This study uses a quantitative approach with 52 respondents. Data were collected through questionnaires and analyzed using multiple regression statistical methods . The analysis technique used to answer the hypothesis is inferential analysis using Partial Least Squares (PLS). The results of the study show that work discipline has a positive effect on employee performance, but increasing work discipline does not necessarily increase employee performance directly. Work discipline has a positive and significant effect on organizational commitment, indicating that the higher the work discipline, the higher the organizational commitment. Financial motivation has a positive and significant effect on employee performance. This study found that organizational commitment positively and significantly affects employee performance. It also serves as a perfect mediator between work discipline and performance, as well as between financial motivation and performance, highlighting its key role in linking these factors to employee performance. This study implies that companies need to improve employee work discipline and financial motivation by paying attention to factors that can improve organizational commitment and employee performance.